Effect of diclofenac sodium on some biochemical parameters of male rats. - Salam H. Al-najjar (University of Thi-Qar Journal, 2019)
The present study aimed to study the effectiveness of diclofenac sodium on some biochemical parameters of male rats. Eighteen of male rats, were utilized in this study, were divided into three groups, the first group (control group) was injected by (0.5ml /animal) of physiological saline. The second group was injected by (0.5ml/animal) of (1mg/kg) of diclofenac sodium. The third group was injected by (0.5ml /animal) of (2mg/kg) of diclofenac sodium. The animals were injected intra peritoneal for 10 days as one dose daily. The results showed no significant differences (p<0.05) in the glucose level of the male rats treated with diclofenac sodium compared with the control group. The results display a significant increase (p<0.05) in levels of cholesterol, triglycerides, liver enzymes (ALT) and (AST) of the male rats treated with diclofenac sodium when compared with control group, which treated with normal physiological saline. In conclusion, diclofenac sodium at high dose causes alterations in biochemical parameters in male rats. These adverse effects may be contributed to oxidative stress induced by the drug. However, the toxic effects of diclofenac sodium could be acute or reversible.